2015
DOI: 10.1111/jocn.12843
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of levels of functioning among Chinese people with severe mental illness: a 12‐month prospective cohort study

Abstract: Mental healthcare services should consider giving priority to self-stigma reduction and empowerment to manage illness especially in this population of patients and their families, thus effectively enhancing their self-care ability to cope with their illness and/or difficult life situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 35 publications
4
22
0
Order By: Relevance
“…Individuals with psychosis are commonly stigmatized (Guner, ; Hopper, Harrison, Janca, & Sartorius, ). Stigmatization is an important factor not only from the community and family members, health professionals and even religious leaders may discriminate mentally ill individuals (Chien, Chan, Yeung, Chiu, & Ng, ; Robson & Gray, ). Coupled to mental disability, physical health problems like weight gain, self‐care problems, not engaging in productive activities, and poor social interaction increases the stigma (Habtamu et al, ; Robson & Gray, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with psychosis are commonly stigmatized (Guner, ; Hopper, Harrison, Janca, & Sartorius, ). Stigmatization is an important factor not only from the community and family members, health professionals and even religious leaders may discriminate mentally ill individuals (Chien, Chan, Yeung, Chiu, & Ng, ; Robson & Gray, ). Coupled to mental disability, physical health problems like weight gain, self‐care problems, not engaging in productive activities, and poor social interaction increases the stigma (Habtamu et al, ; Robson & Gray, ).…”
Section: Discussionmentioning
confidence: 99%
“…In this review, stigma was also among the clearly mentioned hindering factors for subjective recovery (Lam et al, ; Windell & Norman, ). Studies, not included in this review, identified that stigma predicted both symptomatic recovery and subjective recovery (Chien et al, ; Habtamu et al, ; Vass et al, ). Several clear and convincing justifications have been given about how stigma hinders recovery, such as delay in treatment seeking (Chien & Leung, ; Fekadu & Thornicroft, ; Hopper et al, ), and denying the symptoms they have as fear of stigma (Smith et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, mostly from high income countries, identified factors that are associated with functional impairment in people with SMD: socio-demographic characteristics (male sex, older age, single or divorced marital status, urban residence, and lower socio-economic status) [15][16][17][18], illness characteristics (severity of negative and positive symptoms, long duration of untreated psychoses, co-morbid substance abuse, medication side effects, psychotic symptoms in the previous episode, low pre-morbid functioning, the number of prior episodes, prior hospital admissions, and younger age of onset) [13,15,[19][20][21][22][23], social characteristics (lack of social support and stigma) [24,25] and cognitive impairment [4,26,27]. The association of symptom severity, medication side effects, stigma, and cognitive impairment with functional impairment is consistent across studies [17].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of these outcomes would also enable direct comparisons of the benefits of CBFI with those from CBT or other psychosocial intervention studies. In addition, without the components of targeted family outcomes such as expressed emotion or family functioning (Chien, Lam, & Ng, ; Claxton, Onwumere, & Fornells‐Ambrojo, ), and/or some qualitative findings, we can hardly understand the therapeutic mechanism of the effect of CBFI on the interpersonal and family dynamics within the whole family. Besides, all four included studies did not appoint a certified CBT therapist or family therapist to implement the CBFI programmes.…”
Section: Discussionmentioning
confidence: 99%